Revitalizing Malay Royal Town: A Case Study in Alor Setar Kedah. - Jamin, Tuan Ikmal Aizad Tuan Mohd; Shukri, Sharyzee Mohmad; Taib, Idris; Aminuddin, A M R (MAJ - Malaysia Architectural Journal, 2021)
Malaysia's Malay Royal Towns (MRTs) are the outstanding models of early Malay town development going back to the 16th century. MRTs' identity, on the other hand, remains vague today, since they are susceptible by the rise of urbanization and development. This paper aims to study what are the elements of MRT that can be utilized in order to improve the significance impact towards Alor Setar MRT. This research approaches qualitatively which accommodates literature review of previous academic research papers, visual survey, town scape appraisal and semi structured interview. The case study for this research is Alor Setar due to the fundamental factor towards the identity and character of MRT in Malaysia. According to the conclusions of this study, Malay Royal towns play a important role in the development of Malay towns in Malaysia. These towns also exhibit several townscape features that are associated with urban heritage, such as a strong sense of identity, cultural relevance, and architectural importance. The article indicates that traditional conservation methods are inadequate to preserve and retain the entire character of a Malay Royal town. In effort to preserve the uniqueness of the Malay Royal towns, which reflects both local and national identity, a new recommendation of preservation and conservation will be developed.